PERLINDUNGAN HUKUM BAGI OPERATOR TERMINAL DALAM MENGHADAPI PENGADUAN ATAS KECELAKAAN DAN KERUGIAN DI AREA TERMINAL - Dhake, Anselmus; Subekti, Subekti; Astutik, Sri (Gapenas Publisher, 2025)
This study aims to examine legal liability and forms of legal protection for terminal operators in dealing with complaints regarding accidents and losses within the terminal area. The research method used is normative, employing statutory and conceptual approaches. The findings indicate that the liability of terminal operators may arise from negligence or strict liability. Complaints filed by service users are often not only administrative in nature but may also develop into legal disputes. Therefore, terminal operators must be able to perform their role as mediators in non-litigation dispute resolution. Legal protection for operators can be carried out through preventive measures such as the implementation of SOPs and MSS, as well as repressive measures through mediation and legal assistance. In addition, within the context of consumer protection and traffic insurance systems, terminal operators also play a role in supporting the restoration of victims’ rights. This study concludes that terminal operators occupy a strategic position between legal liability and the need for balanced legal protection